Proposed Revision of the Equivalent Axial Load Method for LRFD Steel and Composite Beam-Column Design - Uang, Chia-Ming; Wattar, Samer W.; Leet, Kenneth M. (Engineering Journal, 1990)
After studying the interaction equations that form the basis of the equivalent axial load method for selecting a trial section for a beam-column, the authors propose a series of revisions to the design aids and procedures in the current edition of the LRFD manual. The revisions affect both steel and composite beam-columns. The suggested modifications will permit designers to select a better trialsection, thereby Reducing the computation time for the design of beam-columns.